How is political risk managed and prioritised in the aerospace and defence industry across different institutional contexts? - Ramanathan, Alexandre (2015)
This dissertation investigates the management and prioritisation of political risk in the aerospace and defence industry using a multiple research approach of 2014 corporate annual reports, surveys, interviews and fuzzy set QCA analysis. The aim of the paper sets out to demonstrate that political risk in the aerospace and defence industry extends further than the traditional definitions based on host-country conditions and the social license to operate, but also largely on the dual relationship between the MNE and the government who are primary customers for defence procurement. Empirically, the paper explores the contemporary issues facing these corporations, the strategies employed to mitigate them, the degree of importance political risk plays in the industry and the past and future implications for political risk and FDI. The main findings report that market barriers, changes in government administration, changes in government policies and supply chain disruptions are managed using anticipatory, defensive and proactive strategies. Aerospace and defence political risk also had a high global importance and level of prioritisation explained by three patterns; the protection of home markets, internationalisation into higher risk markets and for maintaining market leading positions in the global industry. Furthermore, FDI has not been restricted since the turn of the 21st century but has been limited to higher risk countries, with the U.S. and UK markets being the most common destination for FDI. The internationalisation to emerging markets across Asia-Pacific, Latin America and Africa however, are set to change this trend and provide future growth to a declining industry.